Perioperative ECX chemotherapy in older adults with gastroesophageal adenocarcinoma. Issue 6 (November 2018) - Tin, Aung Win; Smith, Eleanor; Hepworth, Rebecca; Walker, Julie; Wilson, David; Wadd, Nick
Abstract: Introduction: Perioperative epirubicin, cisplatin and 5-FU or capecitabine (ECF/X) chemotherapy is recognised as a standard of care for patients with resectable gastroesophageal adenocarcinoma; however, there is limited evidence regarding its use in older patients. The aims of this study were to assess the effectiveness and tolerability of perioperative ECX chemotherapy in patients aged ≥70 years-old (group 1) compared with a younger population (group 2), and to assess differences in the histology of these groups. Methods: 212 patients in our centre were treated with neoadjuvant chemotherapy for potentially resectable gastroesophageal adenocarcinoma between February 2009 and January 2014. Seventy patients (33.0%) were aged ≥70 years-old and 142 (67.0%) patients were aged under 70 years-old. Results: In group 1, 57 (81.4%) of patients underwent intended radical oesophagectomy or gastrectomy compared with 106 (74.6%) in group 2 ( p = 0.271). The median overall survival was 35.3 months in group 1 and 30.1 months in group 2, respectively ( p = 0.281). The rates of grade 3 to 4 non-haematological toxicity in groups 1 and 2 were 38.6% and 26.8%, respectively ( p = 0.079). There was no difference in groups 1 and 2 regarding: pT stage, tumour grade, circumferential resection margin involvement, tumour regression grade, vascular invasion, lymphatic invasion and perineural invasion. 74.4% patients in group 2 were node-positive following chemotherapy and surgery compared with 48% in group 1 ( p = 0.0015). Discussion: Selected older adults with gastroesophageal adenocarcinoma treated with perioperative ECX chemotherapy have similar overall survival and likelihood of having radical surgery as younger patients.